(untitled) (JURKAM: Jurnal Konseling Andi Matappa, 2017)
This study aimed to perform relationship between students perceptions on counselling practice with motivational studentâ€™s in to individual counselling process. Data collection was conducted against 288 students in Al Hidayah 1 Vocational School - Jakarta. Data analysis used the correlation coefficient test Gamma and Somers’D. The research findings showed coefficient Gamma and Somers’D test reached 0496 with Zhitung > Ztable or 6,523 > 1.96. It means there is a significant relationship and positive direction between the perceptions of students towards counselling and motivation of students followed individual counselling service